Brunner’ s Gland mucus within the lamina propria of duodenal biopsies A potantial source of diagnostic error - Elif GÜRER İNANÇ; Vildan TAŞKIN; Robert M. GENTA; Rodger C. HAGGİT (Turkish Journal of Gastroenterology, 2019)
-